PRIMARY AMOEBIC MENINGO ENCEPHALITIS- A CASE STUDY: Amoebic Meningo Encephalitis - ., Col Naila Azam; ., Azhar Hayat (Pakistan Armed Forces Medical Journal, 2013)
Primary amoebic meningoencephalitis is caused by the small, pathogenic, free-living amoeba Naegleria Fowleri, Acanthamoeba species and Balamuthia mandrillaris. The first of these, N. Fowleri produces a rare and sporadic acute central nervous system infection that culminates in the death of the host within 5 to 8 days1. The world over about 310 cases have been reported with a high case fatality rate of approximately 95% so far2. Fowler and Carter first described the potential for free-living amoebae to cause disease in 1965, and shortly thereafter, Butt reported several cases in Florida, coining the term primary amoebic meningoencephalitis (PAM) 3.